2006
DOI: 10.1111/j.1530-0277.2006.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold Pressor Task Reactivity: Predictors of Alcohol Use Among Alcohol‐Dependent Individuals With and Without Comorbid Posttraumatic Stress Disorder

Abstract: These preliminary findings demonstrate significant differences between the alcohol-only and the alcohol/PTSD group in predictors of relapse. For the alcohol-only group, reactivity to an acute laboratory stressor may be predictive of subsequent alcohol use. This was not true for the alcohol/PTSD group. Although preliminary, the findings may help shed light on the mechanistic relationship between stress reactivity and increased risk for alcohol relapse and dependence in individuals with and without other Axis I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
65
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 34 publications
6
65
1
1
Order By: Relevance
“…Preclinical studies indicate that specific stress-induced anxiety-like behaviors as well as alcohol cues are associated with increased alcohol selfadministration, and CRF antagonists and noradrenergic agents that decrease brain CRF and reduce norepinephrine, respectively, also decrease stress-induced alcohol reinstatement (Le et al, 1998;Le et al, 1999;Matsuzawa et al, 1998;Le et al, 2000;Liu and Weiss, 2002). In humans, stress and negative affect are known to increase alcohol and drug craving and relapse susceptibility (Brown et al, 1990;Cooney et al, 1997;Breese et al, 2005;Sinha et al, 2006, Brady et al, 2006Sinha, 2007). Koob and colleagues proposed that chronic alcohol and withdrawal-related neuroadaptation produces a negative affect state representing a shift from positive to negative reinforcement mechanisms in addiction (Koob, 2003;Koob et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies indicate that specific stress-induced anxiety-like behaviors as well as alcohol cues are associated with increased alcohol selfadministration, and CRF antagonists and noradrenergic agents that decrease brain CRF and reduce norepinephrine, respectively, also decrease stress-induced alcohol reinstatement (Le et al, 1998;Le et al, 1999;Matsuzawa et al, 1998;Le et al, 2000;Liu and Weiss, 2002). In humans, stress and negative affect are known to increase alcohol and drug craving and relapse susceptibility (Brown et al, 1990;Cooney et al, 1997;Breese et al, 2005;Sinha et al, 2006, Brady et al, 2006Sinha, 2007). Koob and colleagues proposed that chronic alcohol and withdrawal-related neuroadaptation produces a negative affect state representing a shift from positive to negative reinforcement mechanisms in addiction (Koob, 2003;Koob et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in SDs one may expect minimal changes in negative emotion with cue exposure and no negative emotion-related increases in alcohol craving. As stress and negative affect also increase alcohol craving and relapse susceptibility in alcoholics (Cooney et al, 1997;Fox et al, 2007;Breese et al, 2005;Brady et al, 2006), it may be hypothesized that the distress state associated with stressinduced alcohol craving is similar to that associated with alcohol cue-induced craving in alcoholics and not in SDs. Finally, as dysregulation of stress and reward pathways are associated with chronic alcohol abuse, we expected that the stress and cue-induced changes in hedonic state and craving in alcoholics would be accompanied by dysregulation of behavioral distress and physiological responses not observed in SDs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show robust sex variation in the stress-and cue-induced craving state (Brady et al, 2006;Saladin et al, 2012) with women generally reporting significantly higher ratings of anxiety, stress, and negative affect (Back et al, 2005;Chaplin et al, 2008;Fox et al, 2008b;Fox and Sinha, 2009) alongside unique sympathetic dysregulation patterns compared with those of men (Fox et al, 2006;). Preclinical studies have also shown sex diversity with female rats displaying longer HPA-axis activation and greater NE response to stressors compared with male rats (Heinsbroek et al, 1990;Heinsbroek et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For example, raised reward thresholds following drug exposure often provide an index for increased abstinence behaviors (Kenny and Markou, 2005;Schulteis et al, 1995;Kenny et al, 2006). In humans, these have been associated with the protracted withdrawal symptoms documented in early abstinence that include increased irritability, restlessness, depressed mood and anxiety, high cravings (Sinha, 2001;Kampman et al, 1998Kampman et al, , 2001a) and altered stress responses, which have been associated with relapse in both alcoholics (Adinoff et al, 2005;Breese et al, 2005;Brady et al, 2006) and cocainedependent individuals .…”
Section: Introductionmentioning
confidence: 99%